GENETIC FACTORS AND GENETIC METHODS FOR STUDYING INFERTILITY IN MEN - Ibragimova Nadiya Sabirovna; Isakulova Muhabbat Mardanovna; Daminov Feruz Asadullaevich; Tirkasheva Guzal Sirojiddin kizi (TADQIQOTLAR.UZ, 2024)
Annotation. Infertility is a social problem. It is believed that if, with regular sexual activity  without contraception, pregnancy does not  occur within a year, it is necessary to begin examination and, possibly, treatment  of the spouses.  The article presents data on the genetic factors of male infertility and discusses methods that can be used to diagnose it.  An in-depth study of the sperm of infertile men at several levels of organization of genetic material will make it possible to evaluate the information content of each method separately and in combination, as well as to develop an optimal algorithm for diagnostics in order to select the most effective method of treating male infertility.